2016
DOI: 10.1111/cmi.12679
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus nucleoprotein targets subnuclear structures

Abstract: The Influenza A virus nucleoprotein (NP) is the major protein component of the genomic viral ribonucleoprotein (vRNP) complexes, which are the replication- and transcription-competent units of Influenza viruses. Early during infection, NP mediates import of vRNPs into the host cell nucleus where viral replication and transcription take place; also newly synthesized NP molecules are targeted into the nucleus, enabling coreplicational assembly of progeny vRNPs. NP reportedly acts as regulatory factor during infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 98 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…IAV utilizes host nuclear machineries to complete various important life stages, such as transcription and replication, mRNA splicing and trafficking, and vRNP nuclear export. Previous studies have shown that there is an intense functional interplay between IAV and nucleoli ( 25 , 58 ). IAV vRNP hijacks the nucleolar proteins, such as NCL, NPM1, RRP1B, and some ribosomal proteins, to facilitate virus transcription and replication, or vRNP nuclear export ( 25 28 ), of which rRNA processing 1 homolog B (RRP1B) interacts with PB1 and PB2, enhancing viral transcription ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…IAV utilizes host nuclear machineries to complete various important life stages, such as transcription and replication, mRNA splicing and trafficking, and vRNP nuclear export. Previous studies have shown that there is an intense functional interplay between IAV and nucleoli ( 25 , 58 ). IAV vRNP hijacks the nucleolar proteins, such as NCL, NPM1, RRP1B, and some ribosomal proteins, to facilitate virus transcription and replication, or vRNP nuclear export ( 25 28 ), of which rRNA processing 1 homolog B (RRP1B) interacts with PB1 and PB2, enhancing viral transcription ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Their persistence in these populations is largely due to continuous evolution of the viruses, which is driven in influenza A by the natural virus gene reservoir in aquatic birds [118]. As in other influenza viruses, influenza A has a negative-sense ssRNA genome, which is segmented into eight RNAs that exist as virus ribonucleoproteins (vRNPs) in the virus capsid [104,118,119]. Replication and transcription of the virus genome takes places in the host nucleus, by sequestering components of the nuclear machinery [120].…”
Section: Influenza a Virusmentioning
confidence: 99%
“…On the other hand, PML-VI overexpression displayed antiviral effect towards PR8 (H1N1) replication but not remaining IAV strains, indicating isoform-specific antiviral effects of PML [ 82 ]. IAV matrix protein (M1), nucleoprotein (NP), and the nonstructural proteins, NS1 and NS2 (NEP) have been shown to associate with PML NBs, although the functional significance of these associations remains unclear [ 44 , 45 , 46 ].…”
Section: Negative Sense Single Stranded Rna Virusesmentioning
confidence: 99%